Microstructural Evolution Due to One Thermal Cycle in a Superduplex Stainless Steel ASTM A890/A890M-Grade 6A in the As-Weld and Post-Weld Heat Treatment Conditions - Oliveira, Clelia Ribeiro de; Maia, Eloa Lopes; Fonseca, Solange Tamara da; Martins, Marcelo; Avila, Julian Arnaldo [UNESP]; Mei, Paulo Roberto (Univ Fed Sao Carlos, Dept Engenharia Materials, 2019)
During welding of the superduplex stainless steels are exposed to thermal cycles, allowing precipitation of deleterious phases as well as unbalance as the ferrite and austenite phases. This work analyzed the microstructural changes taking place on a plate ASTM A890/A890M - grade 6A steel submitted to arc welding one welding of pass conducted on a flat surface using coated electrode Zeron (R) 100, in the as welded and post-welded heat treatment conditions. Microstructural characterization in the regions base metal, heat affected zone, and fusion zone were conducted by optical microscopy, scanning electron microscopy and X-ray diffraction. The post-weld heat treatment in the fusion zone changed the ferrite/austenite volumetric fraction from 59/41 to 52/48. Cr, Mo and Ni distributions in the fusion zone were altered after the post-weld heat treatment, with the concentration ratio ferrite/austenite being around 1.0; 1.1 and 0.9 to 1.1; 1.4 and 0.7, respectively. In addition, hardness reduced from 300 to 270 HV0.3 at the fusion zone.
Keywords: superduplex stainless steel; ASTM A890/A890M; post-weld heat treatment